2017
DOI: 10.1007/s12110-017-9309-8
|View full text |Cite
|
Sign up to set email alerts
|

Possible Balancing Selection in Human Female Homosexuality

Abstract: A growing number of researchers suggest that female homosexuality is at least in part influenced by genetic factors. Unlike for male homosexuality, few familial studies have attempted to explore maintenance of this apparently fitness-detrimental trait in the population. Using multiple recruitment methods, we explored fecundity and sexual orientation within the pedigrees of 1,458 adult female respondents. We compared 487 homosexual and 163 bisexual with 808 heterosexual females and 30,203 of their relatives. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 77 publications
1
5
1
Order By: Relevance
“…Those nonheterosexual individuals (both men and women) with a greater proportion of samesex partners had a larger reproductive disadvantage (lower birth-year adjusted number of children) relative to exclusively heterosexual participants (Ganna et al, 2019). However, this fitness impairment may be offset by the reported higher number of offspring in nonheterosexual women's kin compared with the kin of heterosexual women (Camperio Ciani, Battaglia, Cesare, Camperio Ciani, & Capiluppi, 2018), indicating sexually antagonistic selection (Luoto et al, 2019a). Sexually antagonistic selection refers to the fact that the attributes favored in one sex are sometimes opposed to those favored in the other sex, which may lead to a fitness detriment when the genotype results in offspring of one sex and a fitness increase when it results in offspring of the other sex (Luoto et al, 2019a).…”
Section: Gwas: Same-sex Sexual Behaviormentioning
confidence: 93%
“…Those nonheterosexual individuals (both men and women) with a greater proportion of samesex partners had a larger reproductive disadvantage (lower birth-year adjusted number of children) relative to exclusively heterosexual participants (Ganna et al, 2019). However, this fitness impairment may be offset by the reported higher number of offspring in nonheterosexual women's kin compared with the kin of heterosexual women (Camperio Ciani, Battaglia, Cesare, Camperio Ciani, & Capiluppi, 2018), indicating sexually antagonistic selection (Luoto et al, 2019a). Sexually antagonistic selection refers to the fact that the attributes favored in one sex are sometimes opposed to those favored in the other sex, which may lead to a fitness detriment when the genotype results in offspring of one sex and a fitness increase when it results in offspring of the other sex (Luoto et al, 2019a).…”
Section: Gwas: Same-sex Sexual Behaviormentioning
confidence: 93%
“…This advantage to the male may be sufficiently large to offset the potential cost of the alleles when they occur in the exclusively homosexual female phenotype (Luoto et al, 2019a). Some evidence for this hypothesis-known as sexually antagonistic selection-has been provided in Italian (Camperio Ciani, Battaglia, Cesare, Camperio Ciani, & Capiluppi, 2018) and Australian samples (Sabia, Wooden, & Nguyen, 2017), where the reproductive success of nonheterosexual women was lower than that of heterosexual women. However, this fitness detriment can be offset by a higher number of offspring in nonheterosexual women's kin compared with the kin of heterosexual women, as reported in the Italian sample (Camperio Ciani et al, 2018).…”
Section: Sexually Antagonistic Selectionmentioning
confidence: 99%
“…Some evidence for this hypothesis-known as sexually antagonistic selection-has been provided in Italian (Camperio Ciani, Battaglia, Cesare, Camperio Ciani, & Capiluppi, 2018) and Australian samples (Sabia, Wooden, & Nguyen, 2017), where the reproductive success of nonheterosexual women was lower than that of heterosexual women. However, this fitness detriment can be offset by a higher number of offspring in nonheterosexual women's kin compared with the kin of heterosexual women, as reported in the Italian sample (Camperio Ciani et al, 2018). Indirect support for the sexually antagonistic selection hypothesis has been recorded in nonhuman animals.…”
Section: Sexually Antagonistic Selectionmentioning
confidence: 99%
“…The logic of the SAGH can be in principle applied also to female homosexuality (Luoto et al, 2019 ). Camperio Ciani et al ( 2018 ) found that the pedigree size and kin fertility of lesbian women were significantly higher than in straight women. If sexually antagonistic selection were responsible for maintaining female homosexuality-associated alleles, we should see increased fertility in lesbian women’s male relatives.…”
Section: Introductionmentioning
confidence: 99%